Assessment for identification of genus Durio spp. from North Maluku Indonesia using three barcode DNA - Sundari,; Wahyudi, Didik; Arumingtyas, Estri Laras; Hakim, Luchman; Rodiyati Azrianingsih, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Durians in North Maluku (Durio spp.) have many local names which are taxonomically ambiguous. These ambiguous can be solved with selecting suitable barcodes for identification. It has been identified for first time using molecular technique. DNA barcode is one technique that can be used for species identification using standard DNA sequences. The objectives of this study is to evaluate the effectiveness of three DNA barcodes to identify and discriminate species of local Durian in North Maluku. A total of 36 samples representing Durian with some local names were collected from three islands (Ternate, Tidore, Jailolo) and were identified using three DNA barcode: matK gene, ITS regions and trnL intron. ITS showed the highest sequencing success, the highest variable site and parsimony informative, most effective for identification using BLASTN NCBI and resulted the most reliable phylogenetic tree. Moreover ITS also has the highest distribution of intraspecific K2P distance (> 0.02) that make ITS can be used as marker to discriminate the Durian. In other hand matK showed the lowest sequencing success but more effective for identification than trnL. In general the results of this research informs that among the three DNA barcodes, i.e. matK, ITS, and trnL, ITS region is the most effective for identifying and discriminating Durio spp.